TINGKAT KETERBACAAN WACANA SAINS DENGAN TEKNIK KLOS - Amas Suryadi (Jurnal Sosioteknologi, 2007)
The quality of text and reference books strongly influences the process and the output of education. The quality of books in this research refers to the level of readability. Based on the previous research to intermediate schools there were so many low readable books that affect the quality of education. With reference to the fact, the purpose of this research was to study and to assess the level of readability of basic science texts for the students of TPB-ITB, Including physics, chemistry, mathematics, and biology. By this research, the level of readability is expectedly found : low, medium, high. The test instruments used were the closure technique and the principle of closure. The closure technique is one of the test instruments with certain procedures, by selectively omitting words. The omitted words are those of the n-number, the fifth until the tenth. The texts that were adopted as the instrument of this research were 33 passages provided to the students of TPB-ITB as the respondents. The criteria of percentage in this closure technique research was of Rankin's and Culhane's. The result of this research was that the level of readability of basic science texts (physics, chemistry, mathematics, and biology) generally belonged to medium category (score : 46.83). The readability of physics texts was high (60.51), that of chemistry was medium (52), of biology medium (43.19), and of mathematics low (31.62). At a glance analysis (needs a further research), language is not the main factor for failing to comprehend the scientific texts. The shape and the small size of letter fonts (10) and the density of lines (1-1.5 space) is one of the causes of unexpected readability level.